Ancinav: análise de uma proposta - Fernandes, Marina Rossato (2014)
This research analyzes the proposal of creation of the National Agency of Cinema and Audiovisual (Ancinav), presented in 2004 by the Ministry of Culture in the form of a project. This was a large proposal that tried to cover the entire audiovisual sector, and not only the cinema. Through its measures, it tried to integrate the sector and upgrade its legislation, and stimulate independent and regional production. The dissertation describes and analyzes the context in which the proposal was written, its goals and its impact. After the analysis, hypotheses about the failure of the project, which was never sent to the Congress, are raised.